2017
DOI: 10.1504/ijmri.2017.085952
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-related performance factors for chemical demolition agents

Abstract: Soundless chemical demotion agents (SCDAs) are percussion-free alternatives to blasting for rock, concrete, and masonry. They hold great potential for selective demolition of and around historic masonry. Although known to be temperature sensitive, to date their performance has not been quantified in ambient environments below 20˚C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Many studies have shown that water/SCDA ratio is inversely proportional to the value and rate of SCDA expansive pressure generating, while higher ambient temperatures and SCDA mixture result to earlier grow of expansive pressures [ [30] , [31] , [32] ]. However, controlling the expansive pressure generating rate and its value by heating of water (befor mixing) or SCDA mixture is not effective, because it leads to an uncontrollable increase in heat, and blowout of SCDA from the borehole.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that water/SCDA ratio is inversely proportional to the value and rate of SCDA expansive pressure generating, while higher ambient temperatures and SCDA mixture result to earlier grow of expansive pressures [ [30] , [31] , [32] ]. However, controlling the expansive pressure generating rate and its value by heating of water (befor mixing) or SCDA mixture is not effective, because it leads to an uncontrollable increase in heat, and blowout of SCDA from the borehole.…”
Section: Introductionmentioning
confidence: 99%
“…20,22,23 Besides, the mechanic properties and cracking behaviors of concrete are associated with many factors, such as aggregate diameter, aggregate distribution, and strain rate. [24][25][26] It has been reported that water/ SCDA ratio is inversely proportional to the expansive pressure generating in SCDA, [23][24][27][28] while higher temperatures (ambient and mix water) result in earlier and greater expansive pressures. 20,23,24,28 Linear relationships between the ambient temperature and time to peak hydration heat was observed by Natanzi et al, 22 and Ish-Shalom et al 29 well explained the correlation between water content, temperature, well diameter, degree of hydration, and expansive pressure development by using Shalom's volume expansion mechanism for SCDA.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] It has been reported that water/ SCDA ratio is inversely proportional to the expansive pressure generating in SCDA, [23][24][27][28] while higher temperatures (ambient and mix water) result in earlier and greater expansive pressures. 20,23,24,28 Linear relationships between the ambient temperature and time to peak hydration heat was observed by Natanzi et al, 22 and Ish-Shalom et al 29 well explained the correlation between water content, temperature, well diameter, degree of hydration, and expansive pressure development by using Shalom's volume expansion mechanism for SCDA. As reported in the aforementioned studies, significant efforts have been devoted aiming to reveal cracking process (crack initiation, propagation, coalescence) and fracturing mechanism of concrete or rock after using SCDA.…”
Section: Introductionmentioning
confidence: 99%